2004
DOI: 10.1177/001698620404800105
|View full text |Cite
|
Sign up to set email alerts
|

Korean Teachers’ Attitudes Toward Academic Brilliance

Abstract: This is a replication of a study designed by Tannenbaum (1962) and repeated by Cramond and Martin (1987) measuring U.S. attitudes toward intelligence by having respondents rate 8 hypothetical students who varied in their combinations of athleticism, effort, and academic ability. This study investigated 132 Korean preservice and in-service teachers’ attitudes on the same measure. Both Korean teacher groups favored athleticism and nonstudiousness over academic brilliance and showed a gender bias by designating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…Yet, interestingly, teacher experience was not a good predictor of attitudes. This confirmed previous research that number of years teaching had little or no association with positive attitudes toward gifted students (Cramond & Martin, 1987;Hanninen, 1988;Lee et al, 2004;Schack & Starko 1990). These results created a gap in the researchers' understanding: if simply having a gifted program yielded support for the program, then why did teachers' experiences with this program (and other experiences) not affect their attitudes toward it?…”
Section: Journal Of Studies In Educationsupporting
confidence: 84%
See 1 more Smart Citation
“…Yet, interestingly, teacher experience was not a good predictor of attitudes. This confirmed previous research that number of years teaching had little or no association with positive attitudes toward gifted students (Cramond & Martin, 1987;Hanninen, 1988;Lee et al, 2004;Schack & Starko 1990). These results created a gap in the researchers' understanding: if simply having a gifted program yielded support for the program, then why did teachers' experiences with this program (and other experiences) not affect their attitudes toward it?…”
Section: Journal Of Studies In Educationsupporting
confidence: 84%
“…One would have guessed that having greater understanding of the unique characteristics and needs of gifted students would lead to teachers displaying more positive attitudes toward gifted students and gifted education. Moreover, teacher experience has been found to have little or no relations to teacher attitudes towards gifted education (Cramond & Martin, 1987;Lee et al, 2004;McCoach & Siegle, 2007;Schack & Starko 1990). To further confirm that teachers' attitudes toward gifted students are not well established, some studies have suggested that pre-service and experienced teachers with specialized training in gifted education tend to have more positive attitudes toward gifted students and are likely to deploy gifted education strategies such as acceleration (Heckenberg, 2001;Megay-Nespoli, 2001;Rash & Miller, 2000).…”
Section: Attitudesmentioning
confidence: 99%
“…The study of Lee et al (2004) disproved this assumption. In this study of 132 Korean preservice and inservice teachers' attitudes towards students, it was found that both Korean teacher groups favored athleticism and nonstudiousness over academic brilliance.…”
Section: Have a Positive Attitude Towards The Giftedmentioning
confidence: 97%
“…High school students were asked to rate each of the hypothetical students who varied in the eight combinations of the dichotomous attributes (brilliant or average; athletic or nonathletic; and studious or non-studious). The derived measurement was replicated (Cramond & Martin, 1987) and adapted in other countries (Carrington, 1996;Lee, Cramond, & Lee, 2016;Rudowicz, 2007). Data from the studies indicated that students do not reject brilliant classmates on the grounds of exceptional intellectual ability.…”
Section: Peers' Perceptions Of High Performers In Academic Fieldsmentioning
confidence: 99%